Fuzzy expert system and its utility in various field - Mishra, Nidhi; Jha, P (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Today’s Fuzzy Logic plays an important role in every field of our life. Fuzzy expert system presents expertise knowledge and it has been effectively applied to solve the problems, classification and modeling in such diverse areas as science, engineering, business and medicine. This paper provides an overview of this fuzzy tool and highlights the basic feature of expert system with fuzzy logic. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->